Ketertindasan dan Perlawanan Perempuan Interseksionalitas dalam Cerpen “Pohon Api” Karya Oka Rusmini - Mustaqim, Andika Hendra (Paradigma: Jurnal Kajian Budaya, 2018)
The main objective of this research is mapping and exploring how the oppression and resistance of the main character (Kekayi) in Oka Rusmini’s short story Pohon Api are manifested through the strategic use of her own intellectuality, not only her beauty; her focus on future visions; and her attempt to garner support from the higher authority to win the competition. This research applied the qualitative approach with content analysis method. This research reveals that Kekayi, the main character in Oka Rusmini’s short story "Pohon Api", is an individual who is at an "intersection". She faces a series of oppression, discrimination, harassment, and unpleasant events which comes from all directions of the "intersection". Then, when a bad treatment is given, it will form a particular pattern that becomes habitual and eventually becomes an ideology. Furthermore, Kekayi possesses the capital to become a strong woman. That power is something given by the Almighty. However, she is also a female learner who always wants to be equal with men.